2018
DOI: 10.3389/fphys.2018.00861
|View full text |Cite
|
Sign up to set email alerts
|

Gait Dynamics in Parkinson’s Disease: Short Gait Trials “Stitched” Together Provide Different Fractal Fluctuations Compared to Longer Trials

Abstract: The fractal analysis of stride-to-stride fluctuations in walking has become an integral part of human gait research. Fractal analysis of stride time intervals can provide insights into locomotor function and dysfunction, but its application requires a large number of strides, which can be difficult to collect from people with movement disorders such as Parkinson’s disease. It has recently been suggested that “stitching” together short gait trials to create a longer time series could be a solution. The objectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 60 publications
0
12
0
Order By: Relevance
“…Another approach that has been recently tested to mitigate the issue of short data series (but also used traditionally while handling outliers; Hausdorff et al, 1997;Herman et al, 2005;Gow et al, 2017) involves concatenating discontinuous sets of time series (Orter et al, 2019). It has been shown that, for positively correlated signals (1.5 > α > 0.5), such concatenation does not affect the scaling behavior on average (Chen et al, 2002;Gow et al, 2017), but the scaling exponent itself might not be consistent (Kirchner et al, 2014;Marmelat et al, 2018). Bartsch et al (2007) proposed a modified DFA method to obtain reliable scaling exponent α values in short time series, but such approaches require further investigation, especially in light of a new study showing that scaling exponent α values from shorter walking trials (e.g., 3 min) do not sufficiently capture the fluctuation dynamics of longer time series (Marmelat and Meidinger, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Another approach that has been recently tested to mitigate the issue of short data series (but also used traditionally while handling outliers; Hausdorff et al, 1997;Herman et al, 2005;Gow et al, 2017) involves concatenating discontinuous sets of time series (Orter et al, 2019). It has been shown that, for positively correlated signals (1.5 > α > 0.5), such concatenation does not affect the scaling behavior on average (Chen et al, 2002;Gow et al, 2017), but the scaling exponent itself might not be consistent (Kirchner et al, 2014;Marmelat et al, 2018). Bartsch et al (2007) proposed a modified DFA method to obtain reliable scaling exponent α values in short time series, but such approaches require further investigation, especially in light of a new study showing that scaling exponent α values from shorter walking trials (e.g., 3 min) do not sufficiently capture the fluctuation dynamics of longer time series (Marmelat and Meidinger, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…This input parameter "n" must be fixed and is generally limited to a range of window sizes, within which the linear relationship between F(n) and n is most stable. Previous studies examining this aspect have recommended the use of 16 to N/9 window size (Damouras et al, 2010), but other sizes have also been utilized (Franz et al, 2015;Gow et al, 2017;Marmelat et al, 2018). Another aspect-the sampling frequency of the 3D kinematics data-can also have a considerable impact on scaling exponent α (a lower sampling frequency may reduce the strength of long-range correlations).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations